Prevalence of in-hospital mortality among adult patients with diabetic ketoacidosis in Ethiopia: a systematic review and meta-analysis of observational studies - Addisu, Zenaw Debasu; Demsie, Desalegn Getnet; Beyene, Dessale Abate; Tafere, Chernet (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetic ketoacidosis (DKA) is one of the most common life-threatening acute metabolic complications of diabetes, typically associated with disability, mortality, and significant health costs for all societies. In Ethiopia, available studies on in-hospital mortality rates of people living with DKA have shown high variability. Therefore, this systematic review and meta-analysis aims to summarize and provide quantitative estimates of the prevalence of in-hospital mortality among adult people living with DKA treated in Ethiopian hospitals.MethodologyA systematic literature search was conducted using MEDLINE, Embase, Google Scholar, Web of Science, and Africa-specific databases. Data were extracted in a structured format prepared using Microsoft Excel. The extracted data were exported to R software Version 4.3.0 for analysis. The I2 test was used to check the heterogeneity between primary studies with a corresponding 95% confidence interval (CI). Based on the test result, a random-effects meta-analysis model was used to estimate Der Simonian and Laird’s pooled effect on in-hospital mortality.ResultThe review included a total of 5 primary studies. The pooled prevalence of in-hospital mortality among people living with DKA who received treatment in Ethiopia hospitals was found to be 7% (95% CI: 1-12). Most of the included studies reported that nonadherence to insulin treatment followed by infection was the most common triggering factor for the development of DKA.ConclusionThe prevalence of in-hospital mortality among people living with DKA was found to be 7%. This figure is unacceptably high compared to other published reports. Nonadherence to insulin treatment or antidiabetic medication and infection were identified as precipitating factors for developing DKA. Therefore, measures must be taken to improve medication adherence and decrease in-hospital mortality by providing ongoing health education on medication usage, effective in-hospital management of hyperglycemia, and increased access to high-quality care.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023432594.